Fractals, diffusion, and relaxation in disordered complex systems (Wiley-Interscience, 2006)
This series provides the chemical physics field with a forum for critical, authoritative evaluations of advances in every area of the discipline. Fractals, Diffusion, and Relaxation in Disordered Complex Systems is a special guest-edited, two-part volume of Advances in Chemical Physics that continues to report recent advances with significant, up-to-date chapters by internationally recognized researchers.